Formation of a trivalent chromium conversion coating on AZ91D magnesium alloy. (1st July 2021) - Qi, Jiantao; Ye, Zonghao; Gong, Ning; Qu, Xuelian; Mercier, Dimitri; Światowska, Jolanta; Skeldon, Peter; Marcus, Philippe
Highlights: Different coating thickness over the Mg alloy matrix and particles was revealed. Cr(OH)3 and ZrO2 were main components evidenced by XPS with Cr/Zr at.% ratio of ∼ 0.5. Coated AZ91D alloy revealed 5.5x increased corrosion resistance. Reduced corrosion current density by a factor of 2 on coated alloy. Abstract: Trivalent chromium conversion (TCC) coating formation on AZ91D magnesium alloy has been investigated using scanning electron microscopy, energy X-ray dispersive spectroscopy (EDS), X-ray photoelectron spectroscoy (XPS). The coating was formed in a commercial SurTec 650 bath. XPS showed that coatings contained mainly Cr, Zr, O, S and F species, which were assigned to hydrated Cr(III) (Cr(OH)3 /CrOOH), ZrO2, Cr2 (SO4 )3, and CrF3, and lower amounts of Mg 2+ and Al 3+ species assigned to oxide, hydroxide and fluoride. The Cr/Zr atomic ratio was around 0.5. The coating was formed above both α matrix and β (Mg17 Al12 ) grain boundary regions, and it was significantly thicker above the cathodic β phase. Raman spectroscopy evidenced the presence of Cr(VI) species, formed due to oxidation of Cr(III) by H2 O2, particularly in the coating above the cathodic sites. Electrochemical impedance spectroscopy revealed that corrosion protection was provided mainly by the barrier layer at the base of the coating, which resulted in a reduction by about a factor of 2 in the anodic and cathodic current density in potentiodynamic polarization curves.